Crisis Standards of Care—More Than Just a Thought Experiment?. Issue 5 (16th September 2021) - Mehta, Anuj B.; Wynia, Matthew K.
Abstract: As described in two articles in the September‐October 2021 issue of the Hastings Center Report, most crisis standards of care (CSC) plans include triage algorithms to guide the allocation of critical care resources to some patients and not others under conditions of extreme scarcity. The plans also include other important CSC strategies, but it is the notion of rationing scarce resources via triage that especially captured the imaginations of ethicists. Vigorous arguments have arisen over whether triage algorithms should be designed to prioritize patients based on predictions of short‐, near‐, or long‐term survival. Additionally, there are ongoing debates about the ability of current algorithms to estimate patient survival accurately enough to be useful in triage and about the role of values like equity in triage protocols. Relatively few debates have noted, however, that while the development of CSC triage protocols has been based in medicine, public health, and ethics, the activation of CSC plans remains a political decision .